Untreated chronic tuberculous salpingitis followed by successful in vitro fertilization conception and congenital tuberculosis - Keane, Joseph; Gleeson, Laura; Mc Laughlin, Anne (My University, 2015)
Female reproductive tract tuberculosis is rarein the developed world and its diagnosis ischallenging. However, this case illustrates theimportance of including female reproductivetract tuberculosis in the differential for any gynae-cological complaint in healthcare workers, dueto the high mortality associated with verticaltransmission.
PUBLISHED
Keywords: Fertilization in vitro; Salpingitis; Tuberculosis; Conception; Congenital tuberculosis